2001
DOI: 10.1016/s0378-1097(00)00498-5
|View full text |Cite
|
Sign up to set email alerts
|

Green fluorescent protein-tagged Edwardsiella tarda reveals portal of entry in fish

Abstract: The application of green fluorescent protein (GFP) to identify the portal(s) of entry of bacterial pathogens in animal hosts was studied using the fish pathogen Edwardsiella tarda and blue gourami, Trichogaster trichopterus. An immersion challenge model was utilized to mimic natural infection conditions in fish. Gastrointestinal tract, gills and the body surface of fish were found to be the sites of entry of virulent E. tarda (PPD130/91) by histological and infection kinetics studies. On the other hand, avirul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
52
0
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(60 citation statements)
references
References 15 publications
7
52
0
1
Order By: Relevance
“…of Ed. tarda PPD130/91 (Ling et al, 2001) or mutant 34. A control group of fish was injected with 0?1 ml PBS.…”
Section: Methodsmentioning
confidence: 99%
“…of Ed. tarda PPD130/91 (Ling et al, 2001) or mutant 34. A control group of fish was injected with 0?1 ml PBS.…”
Section: Methodsmentioning
confidence: 99%
“…The present study revealed that the adherence, as well as the HA, of E. tarda strains FK1051 and KG8401 to HEp-2 cells was markedly inhibited by NANA. It was reported that virulent strains of E. tarda had the ability to adhere to the body mucus of blue gourami Trichogaster trichopterus (Ling et al, 2001). Since NANA is one of the most abundant carbohydrates in the fish mucus (Asakawa, 1983;Wolfe et al, 1998), NANA or related sugar moiety might be a receptor for E. tarda adhesin on the host cells.…”
Section: Discussionmentioning
confidence: 99%
“…E. tarda has the ability to adhere to gill and body surface of fish (Ling et al, 2001). Fimbriae (pili) or hemagglutinins are essential adherence factors usually found in pathogenic bacteria (Finlay and Falkow, 1997;Abraham et al, 1998).…”
mentioning
confidence: 99%
“…In spite of increasing research efforts, relatively little is known about the complex interactions among the coral host, the marine environment, and invading pathogens that lead to disease (Work and Meteyer 2014). The development of tools to effectively visualize pathogens in situ has provided critical insights into complex and highly dynamic host-pathogen interactions in a wide range of disease systems (Valdivia et al 1996;Ling et al 2001;Sawabe et al 2006) and could lead to similar advances in the field of coral disease research.…”
mentioning
confidence: 99%
“…Insertion of green fluorescent protein (GFP) genes into the genomes of microorganisms of interest provides a useful experimental tool to track the behavior of specific microbes as they interact with host tissues and cells (Prasher et al 1992;Chalfie et al 1994;Valdivia et al 1996;Ling et al 2001;Dunn et al 2006). GFPs are nontoxic; therefore, they do not interfere with cell function.…”
mentioning
confidence: 99%